Social Network Analysis in the Legislative Process in the Korean Medical Device Industry - Munjae Lee PhD; Kichan Yoon PhD; Kyu-Sung Lee MD, PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2018)
This study analyzes the legislation process of the Korean government regarding the development of the medical device industry in the perspective of the issue network. It also aims to identify the difference in network structure between conservative and progressive governments and analyze major issues and stakeholders. It examines the network structure in the legislation process of the government to develop and support the medical device industry through social network analysis (SNA). This study conducted a policy network structure analysis of the conservative and progressive governments. SNA was used for the structure analysis, using the contents of newspaper articles as the baseline data related to the medical device industry. We analyze using the 2-mode network analysis that the node centrality is determined by eigenvector centrality. The more nodes with great power (stakeholders, information, resources) it is linked to, the greater power centrality (eigenvector centrality) it will have, which indicates that it has great influence within the network. The conservative government discussed the promotion of the medical device industry led by government departments, focusing on its potential as a future growth engine. On the contrary, the progressive government tended to have fewer stakeholders and issues around the idea, shifting the stakeholders that lead the promotion of the industry from government departments to relevant interest groups, and focusing more on policy issues like transparency than on economic issues. We identify implications to legislate the relevant act by analyzing the relevant stakeholders and issues around legislation, while reinforcing the competitiveness of Korea’s medical device industry in the larger global framework. We believe that this study would comprehensively addresses the pros and cons of the government-led promotion of the medical device industry in Korea, as well as the key issues for stakeholders, which can be applicable to many other societies.